1972
DOI: 10.1017/s0016672300013586
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of metabolism: enzyme studies of theobeseandadiposemutants in the mouse

Abstract: The activity of several enzymes has been determined in the livers of homozygous obese and adipose mice, their normal litter-mates, and phenocopies induced in normal mice by aurothioglucose (ATG) injections.Obese, adipose and ATG mice had higher activities of ATP citrate lyase, malic enzyme (NADP malate dehydrogenase) and pyruvate kinase than normal mice. Heterozygote activities are indistinguishable from wildtype. There was no difference between normal and fat litter-mates in the activity of malate dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Chang et al (1967) found elevated activities of hepatic ACC and FAS in obese Ob/Ob mice compared to their normal littermates. Bulfield (1972) found elevated levels of hepatic ACL, ME and PK in murine obesity caused by the Ob gene, the db"" (previously known as the Ad) gene or an aurothioglucose-induced phenocopy, whereas MDH activity was unaltered. Kaplan & Fried (1973) reported elevated activity of MAL in adipose tissue of Ob/Ob mice.…”
Section: Discussionmentioning
confidence: 95%
“…Chang et al (1967) found elevated activities of hepatic ACC and FAS in obese Ob/Ob mice compared to their normal littermates. Bulfield (1972) found elevated levels of hepatic ACL, ME and PK in murine obesity caused by the Ob gene, the db"" (previously known as the Ad) gene or an aurothioglucose-induced phenocopy, whereas MDH activity was unaltered. Kaplan & Fried (1973) reported elevated activity of MAL in adipose tissue of Ob/Ob mice.…”
Section: Discussionmentioning
confidence: 95%
“…Polyunsaturated fatty acids decrease and saturated fatty acids increase the desaturase activity. Since the carcass lipids of obese mice contain lower proportions of polyunsaturated fatty acids than lean mice (Haessler & Crawford, 1965;Stein et al, 1967;Winand et al, 1969b;Bullfield, 1972), the increased desaturase activity might be explained by a decrease in their inhibitory activity. Food intake also regulates A9-desaturase activity (Inkpen et al, 1969;Lee & Sprecher, 1971) with a decrease during starvation and an increase to Vol.…”
mentioning
confidence: 99%
“…The only consistent change in fatty acid composition, however, is an increase in the proportion of palmitoleic acid (Haessler & Crawford, 1965;Stein et al, 1967;Winand et al, 1969b;Bullfield, 1972) with a compensatory small decrease in several fatty acids but mainly linoleic acid. The obese strains show both a high capacity to deposit dietary fat (Lemonnier et al, 1971) and a higher lipogenic capacity (for a review see Bray & York, 1971), which may maintain the fatty acid composition near normal since mouse diets usually contain a lower proportion of oleic acid than linoleic acid, the reverse of the proportions in adipose tissue.…”
mentioning
confidence: 99%